Treatment outcomes and its associated factors among neonates admitted with sepsis in Hiwot Fana Comprehensive Specialized University Hospital, Harar, Ethiopia - Gezahegn, Betelhem; Abdella, Ahmed; Meseret, Fentahun; Mohammed, Ahmed; Keneni, Mulualem; Asfaw, Tesfaye; Tizazu, Diribsa; Desalew, Assefa (Frontiers in Pediatrics, 2025)
BackgroundSepsis in the neonatal period is a major health challenge in neonatal medicine because of its potential for rapid progression to multi-organ dysfunction, leading to higher morbidity and mortality. Although efforts have been made to advance the outcomes of neonates admitted to hospitals, there is a paucity of data regarding neonatal sepsis treatment outcomes in the study setting. Hence, the study aimed to assess outcomes and prognostic factors of sepsis among neonatal patients admitted to the neonatal intensive care unit in Hiwot Fana Comprehensive Specialized University Hospital in Ethiopia.MethodsA facility-based cross-sectional study was conducted among 311 neonates with sepsis admitted from 1 January 2021 to 30 December 2023. Neonates were selected using systematic random sampling. Relevant data were extracted from medical records using a checklist. The data were entered into EpiData version 4.6 and analyzed using STATA version 17. Bivariable and multivariable logistic regression analyses were performed to identify factors associated with the outcome variable.ResultsEighty-four of 311 patients (27.8%) (95% CI: 22.7%–32.9%) died, while 218 (72.2%) were discharged after improvement. In the multivariable logistic regression analysis, low white blood cell (WBC) count [adjusted odds ratio (AOR) = 4.24, 95% CI: 1.5–12.5], desaturation (aOR = 3.00, 95% CI: 1.6–5.5), pre-term birth (aOR = 2.14, 95% CI: 1.1–4.0), lack of maternal antenatal care (ANC) follow-up (aOR = 2.4, 95% CI: 1.2–4.7), and chorioamnionitis (aOR = 2.8, 95% CI: 1.2–6.5) were significantly associated with neonatal sepsis mortality.ConclusionApproximately one-quarter of patients with neonatal sepsis died. The significant prognostic factors for sepsis were found to be low WBC count, desaturation, lack of ANC visits, and chorioamnionitis. Implementing targeted therapeutic interventions and addressing these prognostic factors could improve treatment outcomes.